CONGENITAL ADRENAL HYPERPLASIA - Miolski, Jelena; Ješić, Maja; Zdravković, Vera (Medicinski podmladak, 2021)
Congenital adrenal hyperplasia is a disease in which a gene mutation, which is inherited autosomal recessively, causes a disorder in the synthesis of enzymes that create glucocorticoids, mineralocorticoids or sex steroids from the adrenal cholesterol. The incidence of the classic form of the disease is from 1: 14000 to 1: 18000 births. The disease in most cases is caused by mutations in the CYP21A2 gene that participates in the synthesis of the enzyme 21 alpha hydroxylase. Due to the lack of enzymes, the synthesis of cortisol is blocked with the accumulation of sex hormones. The classic form of the disease, or a simple virilizing form in which patients lose salt, is diagnosed in the infant period. In the non-classical or mild form of the disease, late onset, patients may be asymptomatic or may present with a milder form of virilization postnatally. The diagnosis is made on the basis of 17 hydroxyprogesterone levels, to determine the deficiency of the enzyme 21 alpha hydroxylase. Complications of the disease are adrenal crisis, hyperglycemia, obesity, elevated blood pressure, infertility, premature entry into puberty. Prenatal therapy is referred to as experimental treatment, while the basis of care is hydrocortisone replacement. In severe forms of the disease, patients are unable to produce enough cortisol in response to stress from gastroenteritis, surgery, trauma, or fever, requiring higher doses of hydrocortisone. In certain cases of genital uncertainty, surgical treatment is necessary. A multidisciplinary team of experts is necessary in adequate surveillance of the disease itself in childhood and adulthood.